Pengaruh Jumlah Sudu Terhadap Optimalisasi Kinerja Turbin Kinetik Roda Tunggal - Pietersz, Richard; Soenoko, Rudy; Wahyudi, Slamet (Rekayasa Mesin, 2013)
Indonesia has a great potential to develop hydropower, because Indonesias mountainous topography and hilly and is drained by numerous rivers (large and small), and in certain areas there are lakes or reservoirs and the potential of water as an energy source. Hydroelectric Power Plant (PLTA) is a technology that has been proven to not harm the environment, support the diversification of energy as renewable energy, support the use of fuel reduction program, and most of the construction using local materials. Kinetic Turbine is one of the options in utilizing the potential of the kinetic energy in the form of velocity, kinetic studies using vertical shaft turbine, blade-shaped bowl that can withstand the flow in order to increase the tangential force generated.Amount ofkineticturbine bladesis one ofthe variablesthat affect therotationandtangentialstyle ofaturbine, so the effecton the value ofthe powerand efficiencyofakineticturbine. The results showedthe influence ofthe number ofbladesonthepowerand efficiency ofbladenumber5,7,9and11,where the number ofblades11have a greater influencethan thenumber ofblade5,7, and9.Keywords: waterturbine, number ofblades, Performance